What constitutes pro-human papillomavirus vaccination videos on social media? Message characteristics, strategies, and theoretical constructs. - Huang, Qian; Harrison, Tyler R; Morgan, Susan E (Health Education Research, 2025)
Videos are essential for promoting human papillomavirus (HPV) vaccinations across populations because videos encompass multiple message characteristics. To understand the patterns of message characteristics, strategies, and theoretical constructs embedded in videos of different types, we coded and analysed 38 variables from 56 videos across five types of pro-HPV vaccination videos (talking head, animation, produced-story, velfie, and mixed-type). We discovered that message characteristics such as redundancy, use of statistics, vividness, video quality, accuracy, authenticity, obtrusiveness, and doctor's recommendations varied across video types. A number of arguments, argument strength, and use of inoculation or forewarning varied by video type, whereas emotional appeals and use of social norms did not. Talking head videos were the lowest in vividness, whereas animation videos were the highest. Animation videos were highly redundant in visual and vocal information and used inoculation strategies to debunk misinformation. Produced-story videos conveyed most information about the susceptibility and severity of HPV-related diseases. Velfie videos had the highest believability and authenticity. Mixed-type videos included various features from the four single-type videos. Findings from this study underscore that because of the differences in the use of theoretical constructs across video types, the potential of different types of videos to affect HPV vaccine uptake may vary.